Volumetric de‐escalation and improved acute toxicity with proton craniospinal irradiation using a vertebral body‐sparing technique. Issue 5 (5th December 2021) - Chou, Brian; Hopper, Austin; Elster, Jennifer; Crawford, John R.; McConnell, Kristen; Chang, Andrew; Mundt, Arno J.; MacEwan, Iain
Abstract: Purpose: In growing children, craniospinal irradiation (CSI) has historically treated the entire vertebral body (VB) to avoid potential long‐term spinal abnormalities. Vertebral body‐sparing proton craniospinal irradiation (VBSpCSI) is a technique that spares the majority of the VB from significant irradiation, and long‐term safety outcomes have been reported previously. This retrospective study reviews the acute toxicity profile of children treated with VBSpCSI in a cohort comparison with photon‐based craniospinal radiotherapy (3DCRT). Methods: Thirty‐eight pediatric CSI patients treated between 2008 and 2018 were retrospectively evaluated for treatment‐related toxicity. Acute toxicity outcomes and acute hematologic profiles were compared according to treatment modality, either VBSpCSI or 3DCRT. Statistical analysis was performed using Fisher's exact test for toxicity. Results: Twenty‐five patients received VBSpCSI and 13 patients received photon CSI. Mean patient age at treatment was 7.5 years (range 2–16). The cohorts were well matched with respect to gender, age, and CSI dose. Patients receiving VBSpCSI had lower rates of grade 2+ gastrointestinal (GI) toxicity (24% vs. 76.5%, p  = .005), grade 2+ nausea (24% vs. 61.5%, p  = .035), and any‐grade esophagitis (0% vs. 38%, p  = .0026). Patients treated with VBSpCSI had lower red blood cell transfusion rates (21.7% vs. 60%, p  = .049) and grade 4+ lymphopenia (33.3% vs. 77.8%, p  = .046). Conclusions: VBSpCSI in children is a volumetric de‐escalation from traditional volumes, which irradiate the entire VB to full or intermediate doses. In our study, VBSpCSI was associated with lower rates of acute GI and hematologic toxicities. Long‐term growth outcomes and disease control outcomes are needed for this technique.